CAR T cells for treating autoimmune diseases - Dimitrios Mougiakakos; Ulrike Koehl; Stephan Fricke; Ulrich Blache; Sandy Tretbar (RMD Open)
Autoimmune disorders occur when immune cells go wrong and attack the body’s own tissues. Currently, autoimmune disorders are largely treated by broad immunosuppressive agents and blocking antibodies, which can manage the diseases but often are not curative. Thus, there is an urgent need for advanced therapies for patients suffering from severe and refractory autoimmune diseases, and researchers have considered cell therapy as potentially curative approach for several decades. In the wake of its success in cancer therapy, adoptive transfer of engineered T cells modified with chimeric antigen receptors (CAR) for target recognition could now become a therapeutic option for some autoimmune diseases. Here, we review the ongoing developments with CAR T cells in the field of autoimmune disorders. We will cover first clinical results of applying anti-CD19 and anti-B cell maturation antigen CAR T cells for B cell elimination in systemic lupus erythematosus, refractory antisynthetase syndrome and myasthenia gravis, respectively. Furthermore, in preclinical models, researchers have also developed chimeric autoantibody receptor T cells that can eliminate individual B cell clones producing specific autoantibodies, and regulatory CAR T cells that do not eliminate autoreactive immune cells but dampen their wrong activation. Finally, we will address safety and manufacturing aspects for CAR T cells and discuss mRNA technologies and automation concepts for ensuring the future availability of safe and efficient CAR T cell products.